Pemilihan Strategi Pemasaran di Era Digital pada Kelompok Ibu PKK Desa Gadingharjo - Antonius Satria Hadi; Ardhi Khairi (Universitas Lancang Kuning, 2020)
Community engagement activities in the form of counseling to mothers of family empowerment and welfare in Gadingharjo Village, Sanden Sub-District, Bantul Regency is aim to provide additional understanding, knowledge, and training to mothers of family empowerment and welfare in Gadingharjo Village in choosing the right marketing strategy in the digital era and industry 4.0 so the products can be marketed widely by utilizing an application-based marketplace that is currently being popular in Gadingharjo Village, namely Shopee application. Counseling aims to provide additional understanding, knowledge, and training to mothers of family empowerment and welfare in Gadingharjo Village in choosing the right marketing strategy in the digital era and industry 4.0 with lecturing, demonstrating, question & answer, and practicing methods. The benefits that can be obtained by participants from community service activities are increased knowledge and understanding of mothers of family empowerment and welfare in Gadingharjo Village about industry 4.0 and about choosing digital marketing strategies by utilizing an application-based marketplace.